A metodologia do professor do ensino religioso e sua contribuição na formação integral do aluno do fundamental II - Torres, Maria Léa Amorim (2015)
The Religious Education discipline (ER), in Brazil, is still being structured both with regard to its program content and for its epistemology and methodology often quite improvised. This study is focused on the Religious Education Teacher Methodology (ER) and its Contribution to the Integral Formation of Basic II student. It s part of the research line: Brazilian religious field, Culture and Society of the Master Degree of religious studies and focusing on a reflection on the teaching and learning methodology adopted by the (RE) teacher in their teaching in elementary II of ten public schools network of the State of Roraima in Boa Vista Capital. As a methodology, there is a historical analysis of the RE process in Brazil and in the State of Roraima and also the types of methods used in educational practice and how these practices have enabled the development of meaningful learning in students, reflecting the formation of concepts and attitudes in their day to day. The analysis makes reference to the teacher's posture from the resources and teaching techniques in the classroom and their reflections on building a critical awareness of students. In this sense, we opted for the literature search, document analysis, participant observation and the application of mixed questionnaire in field research. The design of Religious Education and meaningful learning is backed mainly to the studies of Sérgio Junqueira, Anísia de P. Figueiredo, Paulo Freire, José Carlos Libâneo, Jean Piaget and J. Decius Passos. The concepts of pedagogical innovation, new technologies were the contributions of Antônio Spadaro, Carlos Fino, among others, which brought important contributions to theoretical foundation of this research. Parallel to the theoretical studies were carried out observations in the classroom and the quantitative and qualitative analysis of questionnaires answered by teachers, students, managers and coordinators. In summary, this research intended to analyze, uncover the methodological subtleties in the learning process of Religious Education teacher in the perspective of an innovative pedagogical practice that contributes to the integral formation of the student. The results are not the worst, because there is the use of new techniques and innovative teaching resources in the ER in Boa Vista (RR).